Effectiveness of Mannheim peritonitis index in predicting the morbidity and mortality of patients with hollow viscous perforation - Patil, Vivek A.; Mahapatra, Bibekananda; Panchal, Anuradha; Deolekar, Sandesh (International Journal of Research in Medical Sciences, 2017)
Background: Peritonitis due to hollow viscous perforation is common cause of emergency surgery in India. Despite advances in surgical skills, antimicrobial agents and supportive care the morbidity and mortality of secondary peritonitis remains high. Prognosis and outcome of it depends on many factors which includes patient related factors, disease specific factors and management. Categorizing patients into different risk groups would help in management. Mannheim peritonitis index (MPI) is based on measuring simple clinical parameters in case of hollow viscous perforation. This study was conducted to know efficacy of MPI for predicting morbidity and mortality in hollow viscous perforation. Methods: 50 patients with peritonitis undergoing surgical treatment at Dr. D.Y. Patil medical college, Nerul were included in study. Demographic, clinical data, surgical treatment, outcome were documented and analysed. Results: The morbidity and mortality rate were higher in patients with MPI >29. Surgical site infections were most common complication in patients with MPI <21. Respiratory complications were common in patients with MPI >21. More ICU stay was required in in patients with MPI <21. Conclusions: MPI which is very easy to calculate is simple and effective in predicting morbidity and mortality in patients with hollow viscous perforation.